Teaching for Prosperity? Preparing American Studies Students for the Job Market - Anne Mørk (American Studies in Scandinavia)
This essay explores the challenges faced by American studies faculty and students in Denmark, specifically those preparing for careers in Danish-American relations outside academia. It discusses the evolution of American studies programs at Danish universities, particularly the University of Southern Denmark, in response to criticism regarding the applicability of humanities degrees in the private sector. The essay highlights curricular changes that emphasize practical skills, such as the inclusion of business courses and internships, while maintaining the interdisciplinary foundation of the program. Additionally, it examines the cultural and academic benefits that American studies students bring to business and diplomatic sectors, especially in understanding US-Danish transnational relations. The article also addresses the broader dilemma faced by humanities programs in balancing traditional academic virtues with practical job skills. Finally, it reflects on the shifting global influence of the US and its implications for future American studies faculty and students in Denmark.